Hindbrain V2a Neurons Pattern Rhythmic Activity of Motor Neurons in a Reticulospinal Coculture - Bubnys, Adele; Kandel, Hagar; Kao, Lee Ming; Pfaff, Donald; Tabansky, Inna (Frontiers in Neuroscience, 2019)
As the capacity to isolate distinct neuronal cell types has advanced over the past several decades, new two- and three-dimensional in vitro models of the interactions between different brain regions have sought to expand our understanding of human neurobiology and the origins of disease. These cultures develop distinctive patterns of activity, but the extent to which these patterns are determined by the molecular identity of individual cell types is unclear. To address this question, we developed a simplified culture using two excitatory neuronal subtypes known to participate in the in vivo reticulospinal circuit: HB9+ spinal motor neurons and Chx10+ hindbrain V2a neurons. Here, we report the emergence of cell type-specific patterns of activity in culture; on their own, Chx10+ neurons developed regular, synchronized bursts of activity that recruited neurons across the entire culture, whereas HB9+ neuron activity consisted of an irregular pattern. When these two subtypes were cocultured, Chx10+ neurons recruited the HB9+ neurons into synchronized network bursts, which were dependent on AMPA receptors, thereby recreating an aspect of Chx10+ neurons’ role in driving patterned motor activity. Our results demonstrate that the molecular classification of the neurons comprising in vitro networks is a crucial determinant of their activity. It is therefore possible to improve both the reproducibility and the applicability of in vitro neurobiological and disease models by carefully controlling the constituent mixtures of neuronal subtypes. This work has been uploaded as a pre-print to Biorxiv https://doi.org/10.1101/620674